2022
DOI: 10.3390/safety8010018
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among Bicycle Rider Behaviours, Anger, Aggression, and Crashes in Finland

Abstract: Riding a bicycle is increasingly encouraged as a sustainable transport solution, especially in urban areas. However, safety concerns, both perceived and actual, can significantly lower the willingness to ride among the population. To support cycling planning and policy in the double task of increasing the levels of cycling while mitigating crash risk, there is a need to better understand the behaviours and attitudes of bicycle riders. In this manuscript, we study a cohort of Finnish bicycle riders through four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…In fatal accidents, failed perception was even more pronounced, contributing to 62% of the cases. These findings align with road accident research from various countries, indicating a global trend in the human factors leading to road mishaps [8,[23][24][25][26][27]. In the urban context of Bangkok, a study highlighted several risk behaviors contributing to road accidents.…”
Section: Literature Review 21 Research Backgroundsupporting
confidence: 83%
“…In fatal accidents, failed perception was even more pronounced, contributing to 62% of the cases. These findings align with road accident research from various countries, indicating a global trend in the human factors leading to road mishaps [8,[23][24][25][26][27]. In the urban context of Bangkok, a study highlighted several risk behaviors contributing to road accidents.…”
Section: Literature Review 21 Research Backgroundsupporting
confidence: 83%
“…Building on further previous research conducted both within and outside the Baltic countries, it is noteworthy that O'Hern et al (2021) conducted studies in Finland and Australia on cyclists' behavior and crash involvement, yielding similar results [13,26]. They concluded that cyclists who commit more traffic violations were, consistent with the findings of this initial study with the Latvian population, more prone to making more errors on the road, indicating risky behavior [13].…”
Section: Behavioral Correlates and Safety-related Outcomessupporting
confidence: 70%
“…This finding aligns with previous applications of the instrument in other countries, where cyclists with higher positive behavior scores tended to experience fewer cycling safety-related incidents. Further, in terms of directionality, the association between positive behavior and self-reported crash rates consistently remained negative (e.g., [68][69][70]).…”
Section: Predictive Analysis: Behavioral Contributors To Cycling Crashesmentioning
confidence: 99%